2012
DOI: 10.1002/tesq.35
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Multidimensional and Continuum Models of Vocabulary Acquisition: An Empirical Examination of the Vocabulary Knowledge Scale

Abstract: Second language vocabulary acquisition has been modeled both as multidimensional in nature and as a continuum wherein the learner's knowledge of a word develops along a cline from recognition through production. In order to empirically examine and compare these models, the authors assess the degree to which the Vocabulary Knowledge Scale (VKS; Paribakht & Wesche, 1993), which implicitly assumes a cline model of acquisition, conforms to a linear trait model under the Rasch Partial Credit Model, and determine th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 41 publications
1
17
0
Order By: Relevance
“…Comparison between the treatment conditions in the VKS posttest revealed that both GOs and C(2)Q2 process led to significant gains on the development of vocabulary knowledge and enhanced contextual word knowledge. It was found that the GOs instruction assisted the students to be more successful on meaningful leaps of vocabulary knowledge and enhanced word meaning acquisition (Stewart et al, 2012) compared with the C(2)Q2. The comparison group used a variety of vocabulary instruction activities to learn new words.…”
Section: Effects Of Graphic Organizers On Word-learningmentioning
confidence: 96%
See 3 more Smart Citations
“…Comparison between the treatment conditions in the VKS posttest revealed that both GOs and C(2)Q2 process led to significant gains on the development of vocabulary knowledge and enhanced contextual word knowledge. It was found that the GOs instruction assisted the students to be more successful on meaningful leaps of vocabulary knowledge and enhanced word meaning acquisition (Stewart et al, 2012) compared with the C(2)Q2. The comparison group used a variety of vocabulary instruction activities to learn new words.…”
Section: Effects Of Graphic Organizers On Word-learningmentioning
confidence: 96%
“…The VKS format test has following four responding options/stages. The sample word in the VKS: Public opinion (Stage 1) I do not remember having seen this word before, (Stage 2) I have seen this word before, but I do not know what it means, (Stage 3) I have seen this word before, and I think it means… (synonym or translation), (Stage 4) I can use this word in a sentence… (If you do this selection, please also do "Stage 3") The Stages on the VKS format test present a framework that orient linguistic responds combining performance items and self-report related to vocabulary knowledge (Stewart et al, 2012). Paribakht and Wesche (1993) defined the stages on the VKS ranging from total unfamiliarity to the recognition of the target words or some ideas (i.e., synonym or translation) of the key words' meanings and, the ability to use the key words in a sentence.…”
Section: Vocabulary Knowledge Scalementioning
confidence: 99%
See 2 more Smart Citations
“…One assessment method emphasizing partial word knowledge in test format is the Vocabulary Knowledge Scale (VKS) (Bruton, 2009;Stewart, Batty, & Bovee, 2012;Wesche & Paribakht, 1996). The VKS is a generic instrument for measuring the depth or quality of vocabulary knowledge gain.…”
Section: Assessing Receptive Lexical Learningmentioning
confidence: 99%